Identifying a Missed Opportunity in State Disaster Response: An Analysis of State Housing Finance Agencies' Response to Hurricanes Through the Low-Income Housing Tax Credit. - Weiner, Valerie. (Tufts University. Tisch Library., 2019)
While hurricanes present a significant threat to housing, housing policy and disaster response rarely overlap. State governments regularly use departments unrelated to housing issues to communicate disaster-related priorities, and none consistently address long-term affordable housing safety after disasters. The state disaster-relief programs similarly miss the opportunity to address long-term affordable housing safety by focusing on short-term strategies. The Low-Income Housing Tax Credit Program (LIHTC) and its guiding document the Qualified Allocation Plan (QAP) offer the opportunity to apply disaster response language to affordable housing policy. This thesis aimed to identify whether states use the QAP to this extent, and if so, how strict the change was. Assessing strictness of a change served as a proxy for how strong of an advocate the state was on disaster housing relief, assuming they did make a change. A total of sixty-eight Qualified Allocation Plans, two per State Housing Finance Agency, from the year before and the year after each of the six costliest hurricanes were analyzed. Each was then assessed for possible reasons why a change was made and how strict the change was. The primary mechanisms that could have inspired change were the same as those that may have prevented change: extensive support from federal government, expansion of LIHTC support, developer input, and state prioritization. There were far more states that did not make a change due to these mechanisms than those that did. Only twelve changes were made across the six hurricanes and most of them directly adopted federal policies and priorities with a strong level of strictness and advocacy—rather than tailoring a policy change to their own state needs. Overall, states did not take advantage of the advocacy opportunity within the QAP. States allowed federal policy language to represent their own housing and hurricane-related priorities. These federal policies, however, did not institute long-term affordable housing safety measures specific to each state's affordable housing needs. States should alternatively formulate and express their own priorities through the opportunity provided in the QAP, thus incorporating specific, long-term disaster response into housing policy. Incorporating disaster relief language into housing policies would show that each state considers hurricane damage a local affordable housing problem and is willing to advocate for and invest in a safer living environment for their constituents moving forward.; Thesis (M.A.)--Tufts University, 2019.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Shomon Shamsuddin.; Committee: Jon Witten.; Keywords: Urban planning, Environmental justice, and Public policy.